Differential Genomic Profile in TERT, DSP, and FAM13A Between COPD Patients With Emphysema, IPF, and CPFE Syndrome - Guzmán-Vargas, Javier; Ambrocio-Ortiz, Enrique; Pérez-Rubio, Gloria; Ponce-Gallegos, Marco Antonio; Hernández-Zenteno, Rafael de Jesus; Mejía, Mayra; Ramírez-Venegas, Alejandra; Buendia-Roldan, Ivette; Falfán-Valencia, Ramcés (Frontiers in Medicine, 2021)
Background: Genetic association studies have identified single nucleotide polymorphisms (SNPs) associated with lasting lung diseases such as Chronic Obstructive Pulmonary Disease (COPD) and Idiopathic Pulmonary Fibrosis (IPF), as well as the simultaneous presentation, known as Combined Pulmonary Fibrosis and Emphysema (CPFE) Syndrome. It is unknown if these diseases share genetic variants previously described in an independent way. This study aims to identify common or differential variants between COPD, IPF, and CPFE. Materials and methods: The association analysis was carried out through a case-control design in a Mexican mestizo population (n = 828); three patients' groups were included: COPD smokers (COPD-S, n = 178), IPF patients (n = 93), and CPFE patients (n = 16). Also, two comparison groups were analyzed: smokers without COPD (SWOC, n = 367) and healthy subjects belonging to the Mexican Pulmonary Aging Cohort (PAC, n = 174). Five SNPs in four genes previously associated to interstitial and obstructive diseases were selected: rs2609255 (FAM13A), rs2736100 (TERT), rs2076295 (DSP) rs5743890, and rs111521887 (TOLLIP). Genotyping was performed by qPCR using predesigned Taqman probes. Results: In comparing IPF vs. PAC, significant differences were found in the frequency of the rs260955 G allele associated with the IPF risk (OR = 1.68, p = 0.01). Also, the genotypes, GG of rs260955 (OR = 2.86, p = 0.01) and TT of rs2076295 (OR = 1.79, p = 0.03) were associated with an increased risk of IPF; after adjusting by covariables, only the rs260955 G allele remain significant (p = 0.01). For the CPFE vs. PAC comparison, an increased CPFE risk was identified since there is a difference in the rs2736100 C allele (OR = 4.02, p < 0.01; adjusted p < 0.01). For COPD-S, the rs2609255 TG genotype was associated with increased COPD risk after adjusting by covariables. Conclusion: The rs2736100 C allele is associated with decreased IPF risk and confers an increased risk for CPFE. Also, the rs2076295 TT genotype is associated with increased IPF risk, while the GG genotype is associated with CFPE susceptibility. The rs2609255 G allele and GG genotype are associated with IPF susceptibility, while the TG genotype is present in patients with emphysema.